Aktivitas Penghambatan Enzim Protease 6lu7 Virus Sars-Cov-2 Oleh Senyawa Steroid Glikosida Dari Daun Afrika (Vernonia amygdalina Del.) Secara In Silico - Mainal Furqon; Cut Masyithah Thaib; N Daely, Ruth Christiani (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Background: Vernonia amygdalina Del. Isaplant from the Asteraceae family is a small shrub with dark green leaves and leathery bark that grows predominantly in Africa. This plant contains steroidgly cosides, such: as Vernodalin, Vernolide, Vernolepin, Vernomenin, Vernomydin, Vernodalol, Hydroxylvernolide,11,13-dihydroxylvernodalin, 4,15-dihydrovernodalin, 1,2,3,15,11,13,2’,3’, hexahydrovernodalin, dan 1,2,3,15,11,13,2’,3’-octahydro vernodalin. Sesquiterpene Lakton in African leaves (Vernonia amygdalina) have properties, among others, as antimicrobials. Objective:  The purpose of this study was to determine the inhibition of the SARS-CoV-26LU7 protease enzyme by Sesquiterpen Lakton compounds from African leaves using the in-silico tethering method. Method: The in-silicomooring process is carried out using the PLANTS program and visualized using the MOE 2008 program. The protease enzyme was downloaded through the Protein Data Bank (PDB) with code 6LU7. Two-and three-dimensional models were generated using the Marvin Sketch program. The resulting docking value is evaluated as a result of the docking process. Results: The results showed that the protease 6LU7 enzyme tethering of the SARS-CoV-2 virus could provide valid results in-silico. The Sesquiterpen Lakton compounds from Afri can leaves can inhibit the protease enzyme. The docking result is a bletovisualize of the binding amino acids. Conclusion: In this study, it can be concluded that the Sesquiterpen Lakton compounds from African leaves can inhibit the SARS-CoV-2 virus 6LU7 protease enzyme with a docking score close to the docking score of each comparator drug.